Effects of biological and abiotic factors on dark septate endophytes distribution and heavy metal resistance in different environments - Wang, Zhenzhou; Shi, Wenyi; Chen, Xiuling; Lin, Yuli; Chen, Wenjing; Yao, Li; Sun, Xiang; Li, Xia; He, Xueli (Frontiers in Microbiology, 2025)
Graphical abstract